Assessment of resting energy expenditure in pediatric mitochondrial diseases with indirect calorimetry. Issue 6 (December 2016) - Fiuza-Luces, C.; Santos-Lozano, A.; García-Silva, M.T.; Martín-Hernández, E.; Quijada-Fraile, P.; Marín-Peiró, M.; Campos, P.; Arenas, J.; Lucía, A.; Martín, M.A.; Morán, M.
Summary: Background & aims: Mitochondrial diseases (MD) are the most frequent inborn errors of metabolism. In affected tissues, MD can alter cellular oxygen consumption rate leading to potential decreases in whole-body resting energy expenditure (REE), but data on pediatric children are absent. We determined, using indirect calorimetry (IC), whole-body oxygen consumption (VO2 ), carbon dioxide production (VCO2 ), respiratory quotient (RQ) and REE in pediatric patients with MD and healthy controls. Another goal was to assess the accuracy of available predictive equations for REE estimation in this patient population. Methods: IC data were obtained under fasting and resting conditions in 20 MD patients and 27 age and gender-matched healthy peers. We determined the agreement between REE measured with IC and REE estimated with Schofield weight and FAO/WHO/UNU equations. Results: Mean values of VO2, VCO2 (mL·min −1 ·kg −1 ) or RQ did not differ significantly between patients and controls ( P = 0.085, P = 0.055 and P = 0.626 respectively). Accordingly, no significant differences ( P = 0.086) were found for REE (kcal·day −1 kg −1 ) either. On the other hand, although we found no significant differences between IC-measured REE and Schofield or FAO/WHO/UNU-estimated REE, Bland–Altman analysis revealed wide limits of agreement and there were some important individual differences between IC and equation-derived REE. Conclusions: VO2, VCO2, RQ and REE are not significantly altered in pediatric patients with MD compared with healthy controls. The energy demands of pediatric patients with MD should be determined based on IC data in order to provide the best possible personalized nutritional management for these children. Highlights: In pediatric patients with mitochondrial disorders VO2, VCO2, RQ or REE are not altered. Differences between calorimetry-measured and equation-derived REE occur in pediatric patients with mitochondrial disorders. The REE of pediatric patients with mitochondrial disorders should be determined based on IC.